Homocysteine levels in pediatric renal transplant recipients. - Mota, C. (2003)
Transplant Proc. 2003 May;35(3):1093-5. Homocysteine levels in pediatric renal transplant recipients. Mota C, Fonseca I, Santos MJ, Costa T, Faria MS, Henriques AC, Sarmento AM, Pereira E, Pereira M. Department of Paediatric Nephrology, Maria Pia Children's Hospital, R. da Boavista, 827, 4050-111, Porto, Portugal. ccmotacosta@hotmail.com PMID: 12947872 [PubMed - indexed for MEDLINE